simplify the following :(a-2b+5c)(a-b)-(a-b-c)(2a+3c)+(6a+b)(2c-3a-5b)
Answers
The given expression is:
(a - 2b + 5c)(a - b) - (a - b - c)(2a + 3c) + (6a + b)(2c - 3a - 5b)
We have to simplify the given expression.
Solution:
∴ (a - 2b + 5c)(a - b) - (a - b - c)(2a + 3c) + (6a + b)(2c - 3a - 5b)
= {a(a - b) - 2b(a - b) + 5c(a - b)} - {a(2a + 3c) - b(2a + 3c) - c(2a + 3c)} + {6a(2c - 3a - 5b) + b(2c - 3a - 5b)}
= { - ab - 2ab + 2
+ 5ac - 5bc} - {2
+ 3ac - 2ab - 3bc - 2ac - 3
} +
{12ac - 18 - 30ab + 2bc - 3ab - 5
}
= - ab - 2ab + 2
+ 5ac - 5bc - 2
- 3ac + 2ab + 3bc + 2ac + 3
+
12ac - 18 - 30ab + 2bc - 3ab - 5
= - 19 - 3
+ 3
- 34ab + 0(bc) + 16ac
= - 19 - 3
+ 3
- 34ab + 16ac
∴ (a - 2b + 5c)(a - b) - (a - b - c)(2a + 3c) + (6a + b)(2c - 3a - 5b) = - 19 - 3
+ 3
- 34ab + 16ac
Thus, the simplification of (a - 2b + 5c)(a - b) - (a - b - c)(2a + 3c) + (6a + b)(2c - 3a - 5b) is "- 19 - 3
+ 3
- 34ab + 16ac".
Answer:
Given:
(a-2b+5c)(a-b)-(a-b-c)(2a+3c)+(6a+b)(2c-3a-5b)
Step-by-step explaination:
(a-2b+5c)(a-b)-(a-b-c)(2a+3c)+(6a+b)(2c-3a-5b)
=[-2ab+5ac-ab+2
-5bc]-[2
+3ac-2ab-3bc-2ac-3
]+[12ac-18
-30ab+2bc-3ab-5
]
=-2
-18
+2
-5
-3
-2ab-ab-2ab-30ab-3ab+5ac+12ac+3ac-2ac-5bc-3bc+2bc
=(1-12-18)+
(2-5)+
(-3)+ab(-2-1-2-30-3)+ac(5+12+3-2)+bc(-5-3+2)
= -29-3
-3
-38ab+18ac-6bc